2011
DOI: 10.1016/j.ydbio.2010.10.027
|View full text |Cite
|
Sign up to set email alerts
|

The cell adhesion-associated protein Git2 regulates morphogenetic movements during zebrafish embryonic development

Abstract: Signaling through cell adhesion complexes plays a critical role in coordinating cytoskeletal remodeling necessary for efficient cell migration. During embryonic development, normal morphogenesis depends on a series of concerted cell movements; but the roles of cell adhesion signaling during these movements are poorly understood. The transparent zebrafish embryo provides an excellent system to study cell migration during development. Here, we have identified zebrafish git2a and git2b, two new members of the GIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Antisense RNA probes were labeled with digoxygenenin (Roche DIG RNA labeling kit) to detect spaw expression via RNA in situ hybridization as described (Yu et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Antisense RNA probes were labeled with digoxygenenin (Roche DIG RNA labeling kit) to detect spaw expression via RNA in situ hybridization as described (Yu et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Because Arf proteins have no intrinsic GTPase activity, active GTP-bound Arf proteins require ArfGAP proteins to deactivate them by converting bound GTP to GDP (Randazzo et al, 1994). Mammals express two GIT proteins, GIT1 and GIT2, whereas zebrafish -because they have two GIT2 genes (git2a and git2b) -express three GIT proteins (Yu et al, 2011). Caenorhabditis elegans and Drosophila melanogaster have each only a single GIT gene (git-1 and Git, respectively) (Lucanic and Cheng, 2008;Bahri et al, 2009).…”
Section: Git Proteinsmentioning
confidence: 99%
“…In the β-PIX-deficient mouse, lethality results from defective cell migration during early embryogenesis (Omelchenko et al, 2014). Experiments with GIT2 in Xenopus (Köster et al, 2010) and GIT2a in zebrafish (Yu et al, 2011) demonstrated cell migration defects during gastrulation. GIT1-knockout lethality has been reported to result from poor angiogenesis in the lungs (Pang et al, 2009).…”
Section: Git Proteinsmentioning
confidence: 99%
“…Our findings suggest that NMM-II activity is required for normal myoblast elongation and boundary capture primarily during the early and transitory phases of somite-to-myotome maturation. Previous work has implicated the Paxillin binding partner, Git2, in NMM-II activation and regulation of cell shape during zebrafish epiboly (Yu et al, 2011). Interestingly, activation of NMM-II can promote Integrin activation and ECM fibril formation in newly formed somites (Julich et al, 2015).…”
Section: Discussionmentioning
confidence: 99%